TPP1 is required for TERT recruitment, telomere elongation during nuclear reprogramming, and normal skin development in mice. - Tejera, A; Stagno d'Alcontres, M; Thanasoula, M; Marion, R; Martinez, P; Liao, C; Flores, J; Tarsounas, M; Blasco, M (2010)
The TPP1/ACD protein (hereafter TPP1) is a component of the shelterin complex at mammalian telomeres. Here we find that Tpp1-deficient mouse embryonic fibroblasts (MEFs) show increased chromosomal instability including sister chromatid fusions and chromosomes with multitelomeric signals related to telomere fragility. Tpp1 deletion decreases both TERT (the telomerase catalytic subunit) binding to telomeres in MEFs and telomerase function at chromosome ends in vivo. Abrogation of Tpp1 abolished net telomere elongation in the context of nuclear reprogramming of MEFs into induced pluripotent stem cells, whereas Tpp1 deletion in stratified epithelia of Tpp1(Delta/Delta)K5-Cre mice resulted in perinatal death, severe skin hyperpigmentation, and impaired hair follicle morphogenesis. p53 deficiency rescues skin hyperpigmentation and hair growth in these mice, indicating that p53 restricts proliferation of Tpp1-deficient cells. These results suggest a telomere-capping model where TPP1 protects telomere integrity and regulates telomerase recruitment to telomeres, thereby preventing early occurrence of degenerative pathologies.